Eventisierung bei Flusskreuzfahrten am Beispiel des Flusskreuzfahrtanbieters Dreamlines - Johanna L. P. Jäger; Ina Zur Oven-Krockhaus (IUBH Internationale Hochschule, 2021)
– River cruises, like ocean cruises, are part of a steadily growing market segment. However, the "wow effect" that river cruises have had in recent years is weakening among river cruise guests and they are paying more critical attention to details. River cruise companies are thus faced with the challenge of differentiating themselves from competitors and creating exciting and varied trips through individualisation. One way to achieve this is through eventisation. Through the development of certain themes and experiences, the main product, the cruise, is linked to an event and the special theme becomes the main motive for booking. The empirical study should therefore answer the question: How do customers evaluate event and themed cruises by river cruise companies and what requirements result from this using the example of the largest German online portal for cruises Dreamlines? The analysis in the period from January to December 2019 showed that not all trips are accepted equally by customers. At Dreamlines, of a total of twelve different eventised river cruises, only the Advent, New Year's Eve, Crime dinner, cultural and cycling trips as well as trips with one's own dog were booked. This corre-sponds to only 50 percent of the river cruise themes offered. It also showed that guests' expectations of river cruises with events and theming are only met to a limited extent. The overall satisfaction and perception of quality by the passengers is therefore currently not positively but rather negatively influenced by the event and themed river cruises. According to the analysis, there is potential for action in the areas of: Thematisation of basic services to meet higher expectations, e.g. in the area of gastronomy or cabins, as well as in the creation of emotional added value through authentic experience staging. Other starting points are more transparent com-munication around the event and addressing target groups with potential, e.g. "active couples" or "travellers with dogs". Both groups accept the theme well and show a high level of satisfaction.
Keywords: 330; Flusskreuzfahrten; Eventisierung; Event-und Themenkreuzfahrten; Dreamlines; Zielgruppen; Erlebnisinszenierung